A novel mutation in KIAA0196: identification of a gene involved in Ritscher–Schinzel/3C syndrome in a First Nations cohort. Issue 12 (24th September 2013) - Elliott, Alison M; Simard, Louise R; Coghlan, Gail; Chudley, Albert E; Chodirker, Bernard N; Greenberg, Cheryl R; Burch, Tanya; Ly, Valentina; Hatch, Grant M; Zelinski, Teresa
Abstract : Background: Ritscher–Schinzel syndrome (RSS) is a clinically heterogeneous disorder characterised by distinctive craniofacial features in addition to cerebellar and cardiac anomalies. It has been described in different populations and is presumed to follow autosomal recessive inheritance. In an effort to identify the underlying genetic cause of RSS, affected individuals from a First Nations (FN) community in northern Manitoba, Canada, were enrolled in this study. Methods: Homozygosity mapping by SNP array and Sanger sequencing of the candidate genes in a 1Mb interval on chromosome 8q24.13 were performed on genomic DNA from eight FN RSS patients, eight of their parents and five unaffected individuals (control subjects) from this geographic isolate. Results: All eight patients were homozygous for a novel splice site mutation in KIAA0196 . RNA analysis revealed an approximate eightfold reduction in the relative amount of a KIAA0196 transcript lacking exon 27. A 60% reduction in the amount of strumpellin protein was observed on western blot. Conclusions: We have identified a mutation in KIAA0196 as the cause of the form of RSS characterised in our cohort. The ubiquitous expression and highly conserved nature of strumpellin, the product of KIAA0196, is consistent with the complex and multisystem nature of this disorder.